Kant on Republicanism - Gałkowski, Jerzy W. (Roczniki Filozoficzne, 2023)
The problem of republicanism belongs to the set of issues of politics that Kant addressed towards the end of his life. The development and perfection of man does not lie in the action of human nature, which is constant, but in the person’s action of freedom. The ultimate goal of human’s development is eternal peace. The condition for the attainment of this supreme goal is the establishment of a republican system. Kant illustrates his account of historical progress with the example of the French Revolution. Although he is a staunch opponent of every revolution because of the means of its enforcement, he views its effects positively. He thinks it expressed the right of the people to freely give themselves a civic system that is legitimate and recognised as good: a republican system, which is the best of all systems. Republicanism determines the form of the state, and, more importantly the form of government, one that is characterised by the separation of legislative and executive powers, and by three essential principles: 1) the principle of freedom for all citizens; 2) the principle of dependence of all on the universal law; 3) the principle of equality of all citizens.